Genetic variation and structure of complete chloroplast genome in alien monoecious and dioecious Amaranthus weeds - Han Xu; Ning Xiang; Wei Du; Junhua Zhang; Yongjiang Zhang (Scientific Reports, 2022)
Abstract Amaranthus is a complex taxon with economic importance as well as harmful weeds. We studied the genetic variation and structure of the chloroplast genomes of 22 samples from 17 species of three subgenera. It was found that the length of the chloroplast genome of Amaranthus varied from 149,949 bp of A. polygonoides to 150,757 bp of A. albus. The frequencies of SNPs and InDels in chloroplast genomes were 1.79% and 2.86%, and the variation mainly occurred in the non-coding regions. The longest InDel was 387 bp, which occurred on ycf2, followed by 384 bp InDel on psbM-trnD. Two InDels in ndhE-I on the SSC make the three subgenera clearly distinguished. In LSC, SSC and IRs regions, there were four 30 bp forward and reverse repeats, and the repeats in SSC and LSC were in nearly opposite positions in circular genome structure, and almost divided the circular genome into symmetrical structures. In the topological tree constructed by chloroplast genome, species in subgen. Amaranthus and subgen. Acnida form monophyletic branches separately and cluster together. A. albus, A. blitoides and A. polygonoides were separated from subgen. Albersia, and the rest of subgen. Albersia were clustered into a monophyletic branch. The rpoC2, ycf1, ndhF-rpl32 were good at distinguishing most amaranths. The trnk-UUU-atpF, trnT-UGU-atpB, psbE-clpP, rpl14-rps19, and ndhF-D can distinguish several similar species. In general, the chloroplast genome is of certain value for the identification of the similar species of Amaranthus, which provides more evidence for clarifying the phylogenetic relationships within the genus.